Non-invasive biomarkers of liver inflammation and cell death in response to alcohol detoxification - Neuman, Manuela G.; Müller, Johannes; Mueller, Sebastian (Frontiers in physiology, 2021)
Introduction: Alcohol-related liver disease (ALD) represents the most common liver disease worldwide, however, the underlying molecular mechanisms are still poorly understood. Namely centrilobular inflammation and programmed cell death are characteristic to ALD and it remains to be elucidated why they persist despite the absence of alcohol. Aims: To study the repair effects of alcohol withdrawal on non-invasive cytokines, apoptotic, growth and angiogenic biomarkers in a cohort of heavy drinkers and the role of cirrhosis. Methods: M30, M65, IL-6, IL-8, TNF-alpha, TGF-beta and VEGF were measured in 114 heavy drinkers. The role of alcohol detoxification was investigated in 45 patients and liver histology was available in 23 patients. Fibrosis stage and steatosis were assessed by measuring liver stiffness (LS) and controlled attenuation parameter (CAP) in all patients using transient elastography (FibroScan, Echosens, Paris). Mean observation interval between the measurements was 5.7 ± 1.4 days. Results: Patients consumed a mean of 204 ± 148 g/day alcohol with a heavy drinking duration of 15.3 ± 11.0 years. Mean LS was 20.7 ± 24.4 kPa and mean CAP was 303 ± 51 dB/m. Fibrosis distribution was F0 - 38.1%, F1-2 - 31%, F3 - 7.1% and F4 - 23.9%. Apoptotic markers M30 and M65 were almost five times above normal. In contrast, TNF-alpha, IL-8 and VEGF were only slightly elevated. Patients with manifest liver cirrhosis (F4) had significantly higher levels of M30, M65, IL-6 and IL-8. Histology features such as hepatocytes ballooning, Mallory-Denk bodies, inflammation and fibrosis were all significantly associated with elevated LS. During alcohol detoxification, LS, transaminases, TGF-beta, IL-6, IL-8 and VEGF decreased significantly. In contrast, no significant changes were observed for M30, M65 and TNF-alpha and M30 even increased during detoxification in non-cirrhotic patients. Profibrogenic cytokine TGF-beta and pro-angiogenic cytokine VEGF showed a delayed decrease in patients with manifest cirrhosis. Conclusion: Patients with alcohol-related cirrhosis have a pronounced apoptotic activity and a distinct inflammatory response that only partly improves after one week of alcohol detoxification. Alcohol withdrawal may represent an important approach to better dissect the underlying mechanisms in the setting of alcohol metabolism.